2022
DOI: 10.1177/09576509221125863
|View full text |Cite
|
Sign up to set email alerts
|

Wind turbine power prediction via deep neural network using hybrid approach

Abstract: Due to the chaotic nature of wind speed, short-term wind power prediction is a challengeable one. A reliable and accurate wind power prediction model is necessary for the wind turbine industry. Based on their improved ability to cope with complicated nonlinear issues, an increasing number of deep learning-based models are being explored for wind power prediction as artificial intelligence technologies, especially in deep neural networks. In this research, the wind power prediction model is divided into three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Ahilan D T et al proposed a hybrid SOA for short-term wind power prediction, which specified the weight optimization points of deep neural networks in wind power prediction and reduced the time required for the same operation. The results indicated that the proposed method had certain effectiveness [21]. G. Hu et al addressed the problems of low optimization accuracy, slow search speed, and susceptibility to local optima in traditional SOA algorithms by introducing chaotic mapping and imitation cross mutation strategies, and proposed an improved hybrid strategy SOA algorithm [22].…”
Section: Related Workmentioning
confidence: 99%
“…Ahilan D T et al proposed a hybrid SOA for short-term wind power prediction, which specified the weight optimization points of deep neural networks in wind power prediction and reduced the time required for the same operation. The results indicated that the proposed method had certain effectiveness [21]. G. Hu et al addressed the problems of low optimization accuracy, slow search speed, and susceptibility to local optima in traditional SOA algorithms by introducing chaotic mapping and imitation cross mutation strategies, and proposed an improved hybrid strategy SOA algorithm [22].…”
Section: Related Workmentioning
confidence: 99%